2012
DOI: 10.3382/ps.2012-02474
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Bacillus subtilis ANSB060 on egg quality, biochemical and histopathological changes in layers exposed to aflatoxin B1

Abstract: Bacillus subtilis ANSB060 from the fish gut had strong ability to detoxify aflatoxins. The aim of this research was to investigate the protective effect of B. subtilis ANSB060 (ANSB060) on egg quality and biochemical and histopathological changes of liver and kidney in laying hens when exposed to aflatoxin B(1). Treatments (C20, C40, and C60) were prepared by substituting corn contaminated by aflatoxin B(1) (AFB1) at different proportions (20, 40, and 60%) for normal corn in basic diets. The aflatoxin degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 26 publications
5
19
0
2
Order By: Relevance
“…A similar finding was demonstrated in birds subjected to AFB1, which contributed to the toxicological and pathological effects of the toxin (Yarru et al, 2009). Consistent with our results, several reports have demonstrated that the toxic effects of AFB1 involved decreased antioxidant capacity (Tu¨rkez et al, 2011), for example, AFB1 significantly decreased the activities of antioxidase, including GPx, in the broiler spleen (Wang et al, 2013), in rat liver, and kidney (Ravinayagam et al, 2012;Sivanesan and Hazeena Begum, 2014) and in laying hen's liver (Ma et al, 2012).…”
Section: Figuresupporting
confidence: 94%
“…A similar finding was demonstrated in birds subjected to AFB1, which contributed to the toxicological and pathological effects of the toxin (Yarru et al, 2009). Consistent with our results, several reports have demonstrated that the toxic effects of AFB1 involved decreased antioxidant capacity (Tu¨rkez et al, 2011), for example, AFB1 significantly decreased the activities of antioxidase, including GPx, in the broiler spleen (Wang et al, 2013), in rat liver, and kidney (Ravinayagam et al, 2012;Sivanesan and Hazeena Begum, 2014) and in laying hen's liver (Ma et al, 2012).…”
Section: Figuresupporting
confidence: 94%
“…Eles relatam que isso ocorreu pela possível presença de enzimas que realizam a degradação dessa micotoxina. Ma et al (2012) verificaram que Bacillus subtilis (ANSB060), obtidos do intestino de peixes, possuem forte capacidade de desintoxicar aflatoxinas. Dessa maneira, avaliaram a qualidade do ovo e alterações bioquímicas séricas e histopatológicas do fígado e rim de galinhas poedeiras, quando expostas à aflatoxina B1.…”
Section: Controle Das Micotoxinas -Enzimas Microbianasunclassified
“…Similarmente, Tejada-Castañeda et al (2008) demonstraram a viabilidade da utilização de Nocardia corynebacterioides NRRL24037 para detoxificação de milho contaminado com aflatoxina, uma vez que o microrganismo não causou prejuízo ao desempenho das aves e reduziu parcialmente o nível de contaminação da ração. MA et al (2012) relataram que a bactéria Bacillus subtilis ANS060, isolada de intestino de peixes, possui uma forte habilidade em detoxificar aflatoxinas. Os autores observaram que a adição dessa estirpe na ração contaminada de poedeiras comerciais diminuiu os efeitos tóxicos das aflatoxinas no fígado e rins, além de aumentar a atividade de enzimas antioxidantes e restaurar a síntese proteica hepática.…”
Section: Utilização De Enzimas Microbianasunclassified